2004
DOI: 10.2169/internalmedicine.43.493
|View full text |Cite
|
Sign up to set email alerts
|

Thymic Squamous Cell Carcinoma Producing Parathyroid Hormone-related Protein and CYFRA 21-1

Abstract: A 54-year-old man was admitted to our hospital because of dyspnea. Radiographic examination showed an anterior mediastinal mass and pericardial effusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Thymomas are frequently associated with characteristic autoimmune phenomena like myasthenia gravis or pure red cell aplasia, which normally do not occur in thymic carcinomas. However, sporadic cases of polymyositis or hypercalcemia have been encountered in the latter [ 6 – 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thymomas are frequently associated with characteristic autoimmune phenomena like myasthenia gravis or pure red cell aplasia, which normally do not occur in thymic carcinomas. However, sporadic cases of polymyositis or hypercalcemia have been encountered in the latter [ 6 – 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several reports have described that elevated CYFRA 21‐1 level is associated with thymic carcinoma. Yoshiike et al 28 reported a case of thymic squamous cell carcinoma with an extremely high CYFRA 21‐1 level of 310 ng/ml (normal level, <3.5 ng/ml). However, the status of CYFRA 21‐1 after treatment has not yet been described.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, PTHrP was detected in numerous tumour types like prostate cancer (20-22), epithelioid leiomyosarcoma (23), uterine carcinoma (24), cancer of the exocrine pancreas (10), pancreatic neuroendocrine tumour (25,26), squamous cell carcinoma (27-31), medulloblastoma (32), craniopharingioma (33), rhabdomyosarcoma (34,35), haematological tumors (36)(37)(38), tumors of the neck and head (39)(40)(41)(42), carcinoma of ovary (43,44), gallbladder carcinoma (45), cholangiocellular carcinoma (46,47), colorectal adenocarcinoma (48-52), carcinoma of the stomach (53), and melanoma (54).…”
Section: Parathyroid Hormone-related Proteinmentioning
confidence: 99%